The politics and economics of European monetary integration - Tsoukalis, Loukas (London : Allen & Unwin, 1977)
This book is a modified version of a doctoral thesis approved by the University of Oxford in February 1976. It examined the history of Economic and Monetary Union (EMU) in the European Community, the politics of the parties involved and the conflicts of interest created in the political and economic environment within which issues of monetary union take place.
A revision of the author's thesis, Oxford, 1976.
Includes bibliographical references and index.
usc 23/06/2017
Loans
Keywords: Monetary policy; Monetary unions; Europe--European Economic Community countries